ECOLOGICAL STATE EVALUATION OF MINE FIELD OF THE SOTK GOLD-POLYMETALLIC DEPOSIT (Proceedings of the YSU C: Geological and Geographical Sciences, 2006)
The research allowed to evaluate the nature and degree of pollution with heavy and toxic metals of South-West flang soil in Sotk gold-polymetallic mine field. this issue is very urgent. According to the pollution criterion the data of soil types concern the high pollution category. The main polluting elements were discovered. To assess the impact of technogenesis on biosphere, additional complex eco-geochemical investigations are suggested.
Keywords: Sotk gold-polymetallic mine field; heavy and toxic metals; pollutant elements; technogenesis on biosphere